Surveillance of neo-squamous epithelium after ablation of Barrett's esophagus: is it better to use jumbo over standard biopsy forceps?. Issue 7 (28th May 2020) - Duvvuri, Abhiram; Desai, Madhav; Srinivasan, Sachin; Chandrashekar, Viveksandeep Thoguluva; Vennelaganti, Sreekar; Vennalaganti, Prashanth; Jani, Bhairvi; Lim, Diego; Ciscato, Camilla; Spaggiari, Paola; Consolo, Pierluigi; Porter, Jaime; et al.
Summary: Background and Aims: As obtaining adequate tissue on biopsy is critical for the detection of residual and recurrent intestinal metaplasia/dysplasia in Barrett's esophagus (BE) patients undergone Barrett's endoscopic eradication therapy (BET), we decided to compare the adequacy of biopsy specimens using jumbo versus standard biopsy forceps. Methods: This is a two-center study of patients' post-radiofrequency ablation of dysplastic BE. After BET, jumbo (Boston Scientific ©, Radial Jaw 4, opening diameter 2.8 mm) or standard (Boston Scientific ©, Radial Jaw 4, opening diameter 2.2 mm) biopsy forceps were utilized to obtain surveillance biopsies from the neo-squamous epithelium. Presence of lamina propria and proportion of squamous epithelium with partial or full thickness lamina propria was recorded by two experienced gastrointestinal pathologists who were blinded. Squamous epithelial biopsies that contained at least two-thirds of lamina propria were considered 'adequate'. Results: In a total of 211 biopsies from 55 BE patients, 145 biopsies (29 patients, 18 males, mean age 61 years, interquartile range [IQR] 33–83) were obtained using jumbo forceps and 66 biopsies (26 patients, all males, mean age 65 years, IQR 56–76) using standard forceps biopsies. Comparing jumbo versus standard forceps, the proportion of specimens with any subepithelial lamina propria was 51.7% versus 53%, P  = 0.860 and the presence of adequate subepithelial lamina propria was 17.9% versus 9.1%, P  = 0.096 respectively. Conclusions: Use of jumbo forceps does not appear to have added advantage over standard forceps to obtain adequate biopsy specimens from the neo-squamous mucosa post-ablation.